EHR System MojTermin: Implementation and Initial Data Analysis - Velinov, Goran; Jakimovski, Boro; Lesovski, Dragan; Ivanova Panova, Daniela; Frtunik, Dalibor; Kon-popovska, Margita (My University, 2015)
Healthcare informatics has gained importance over the last several years. E-health systems on a national level have already been implemented in most European countries. Data generated by these systems are used to improve healthcare policies as well as health services. In this paper we present the system MojTermin (MyAppointment), as it evolves from a healthcare appointment engine to a complete national e-health system. We also present preliminary results from data gathered during the implementation of this system. In our analysis, we show how the system aided in the discovery of several specific socio-cultural phenomena, which led to governance changes in order to optimize resourses and raise the quality of the entire national healthcare system.